Maria Rosa: fome, fé e resistência na Guerra do Contestado - Maciel, Marcelo Johny (2017)
This monograph paper was developed from a methodology basis of Social Sciences, with emphasis in political Sciences and added to the contributions of history, anthropology and literature. The main objective is to present the most important aspects of the War of Contestado within a linear process to the formation of the first refuge which took place in the region, considering the social and symbolic elements important in the consolidation of the political leaderships manifested in this conflictive period. The War of Contestado unlikely the other conflicts which are generally remembered by the male engagement in the resistance role, represents the normality with the youth and of the women participation. Despite the effort of the State in silencing the individuals who featured the fight in defense of the legitimacy of the land, the result was proportional to the oppression which the countrymen suffered, developed different ways of the strategies through the collective awareness. The formation of the Contestado took place in large scale by the forced migration of the “gaúchos” – countrymen from the State of Rio Grande do Sul – who were expelled from their homeland by the State in different moments. The Contestado was in the beginning a commercial post between Sao Paulo and Rio Grande do Sul State, afterwards the conflicts involving the “gauchos”, many people searched for this region to restart their lives believing that they would have a distance from the State. Regarding the Republic and the project of modernization applied in the mid-south states with the railway tracks, areas such as the Contestado turned out to be valuable for the important market, becoming the desire between the States of Santa Catarina and Parana. The dispute between these states affected directly the countrymen who recovered rapidly all the resources acquired in other conflicts and started to resist all the interests of the capital. This dispute for the space regarded by the countrymen as sacred, qualified the women as reference in refuges due to the possession of the best resources. Among all, Maria Rosa had an important role of absolute leadership in the acutest moment of the war. In order to have a better understanding of how this process happened, it was necessary a rigorous documentation analysis and with the support of the literature it was possible to understand that the process which led to Maria Rosa to the power comes from a very recent history; the female role in the Farroupilha and in the Rio Grande do Sul Federalist Revolution both contribute meaningfully to break the idea of the Contestado was an exception and this was the main objective of this research